Mobility, independent agency, and cosmopolitan settlement: Evidence from Chinese senior undergraduates - Tang, Hui; Chen, Gengyao; Liu, Zhijun; Zhao, Ran; Lu, Cheng; Su, Yanhua (Frontiers in Psychology, 2022)
Cosmopolitan cities share similarities with historical frontiers, including potential opportunities for economic success, high social mobility, weakened traditional conventions, and adventure and novel experiences. Individuals with high independence typically prefer to settle in cosmopolitan cities. However, previous research testing this cosmopolitan settlement hypothesis did not consider the influence of relational mobility and residential mobility. Moreover, the mechanisms that drive people to prefer cosmopolitan cities remain unclear. This study examines the relationships among independence, relational mobility, residential mobility, and preference for cosmopolitan cities among 296 Chinese senior undergraduates. The results indicate that: (1) independence remains a positive predictor of the preference for cosmopolitan cities above and beyond relational mobility, residential mobility (i.e., history, state, and intention), and other covariates; (2) intention of residential mobility also positively predicts preference for cosmopolitan cities when controlling for related covariates; and (3) relational mobility indirectly predicts perceived preference for cosmopolitan cities through dependence. This research underscores the importance of identifying the factors and mechanisms affecting cosmopolitan settlement.